Aluminum effects on the uptake and utilization of macronutrients in two rice cultivars - Mendonça, Renilton Joaquim de; Cambraia, José; Oliveira, Juraci Alves de; Oliva, Marco Antonio (Pesquisa Agropecuaria Brasileira, 2003)
To evaluate the effect of Al on the uptake and utilization of some macronutrients, the rice cultivars Fernandes and Maravilha, respectively tolerant and sensitive to this metal, were exposed to Al in nutrient solution for 20 days, and the contents, uptake and efficiency of utilization of P, K, Ca and Mg were determined. The uptake and the contents of these macronutrients decreased in the presence of Al in the aerial parts and roots of both cultivars, especially at the higher Al concentration and in the Al sensitive cultivar. The macronutrient contents more reduced by Al in the roots were K > Mg > P and Ca > Mg=K>P and in the aerial parts were Mg > Ca > P and Mg > Ca > P > K in the tolerant and sensitive cultivars, respectively. The macronutrients uptake more reduced by Al were Mg > Ca > P > K in both cultivars. In the presence of Al, the tolerant cultivar showed higher efficiency of utilization of all studied macronutrients. The utilization indices of P, Ca and Mg increased in the tolerant cultivar, but decreased for P and K, increasing only for Mg in the sensitive cultivar. The results suggest that the differential tolerance of these rice cultivars to Al may be due to their differences in uptake, ability to keep adequate concentrations and to use these macronutrients with higher efficiency, especially Mg, Ca and phosphorus.